Perawatan Lansia: Menerjemahkan Peraturan Nasional ke dalam Program Lokal di Kota Yogyakarta - Yuni Hastuti; Muhadjir Darwin; Sukamdi Sukamdi; Agus Heruanto Hadna (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2018)
One of the important issues related to the elderly is the elder people is significantly increase in the number. In accordance to that, the problems faced by the elderly are also increase and vary. This study aims to examine whether the regulation as the basis for policy formulation and elderly care programs is sufficient. Besides that, this study also tends to identify the translating of existing regulations into elderly care programs in City of Yogyakarta. To answer these problems, research was conducted by combining three ways: document study, survey and qualitative study through in-depth interviews with stakeholders in City of Yogyakarta.The results show that normatively regulation at the national and provincial levels are sufficient as a basis for the formulation of elderly care policies. Nevertheless another serious problem is the operationalization of regulations into the program. The mandate in the law or other regulations was not fully be fulfilled at the level of programs and activities. At the operational level, several programs that have been carried out in City of Yogyakarta have been able to respond to the needs of the elderly. The survey shows that most of the elderly need to join a gathering of fellow seniors and this has been responded to by Rusela program (healthy elderly homes). However there are still some needs, especially regarding the economy and health that have not been responded optimally.